Characterization of a Novel blaKLUC Variant With Reduced β-Lactam Resistance From an IncA/C Group Plasmid in a Clinical Klebsiella pneumoniae Isolate - Li, Pingping; Shen, Kai; Zhang, Ying; Ying, Jianchao; Zhu, Tingyuan; Liu, Yabo; Xu, Lei; Lin, Chaoqing; Zhang, Kaibo; Li, Peizhen; Lu, Junwan; Li, Kewei; et al. (Frontiers in Microbiology, 2018)
Similar to other CTX-M family enzymes, KLUC is a recently identified and emerging determinant of cefotaxime resistance that has been recovered from at least three Enterobacteriaceae species, including Kluyvera cryocrescens, Escherichia coli, and Enterobacter cloacae. Whether this extended-spectrum β-lactamase (ESBL) has been disseminated among commonly isolated Enterobacteriaceae is worthy of further investigation. In this study, we screened 739 nosocomial Enterobacteriaceae isolates (240 Klebsiella pneumoniae and 499 E. coli strains) and found that one K. pneumoniae and four E. coli isolates harbored the blaKLUC gene. Three blaKLUC determinants isolated from E. coli were entirely identical to a blaKLUC-3 gene previously recovered in the same hospital. PFGE of four blaKLUC-harboring E. coli strains showed that prevalence of these determinants was most likely mediated by horizontal gene transfer but not clonal dissemination. However, the variant isolated from K. pneumoniae belonged to a novel member of the KLUC enzyme group. This newly identified enzyme (KLUC-5) has an amino acid substitution compared with previously identified KLUC-1 (G18S) and KLUC-3 (G240D). Antimicrobial susceptibility tests showed that KLUC-5 significantly reduced resistance activity to almost all the selected antimicrobials compared to previously identified KLUC-3. Site-directed mutagenesis showed that blaKLUC-5-D240G and blaKLUC-5-S18G significantly enhanced the MIC against its best substrate. Conjugation and S1-PFGE indicated that blaKLUC-5 was located on a transferable plasmid, which was further decoded by single-molecule, real-time sequencing. Comparative genome analysis showed that its backbone exhibited genetic homology to the IncA/C incompatibility group plasmids. A transposable element, ISEcp1, was detected 256-bp upstream of the blaKLUC-5 gene; this location was inconsistent with the previously identified blaKLUC-1 but congruent with the variants recovered from E. coli in the same hospital. These data provide evidence of the increasingly emerging KLUC group of ESBLs in China.